Emotional reactions to deviance in groups: the relation between number of angry reactions, felt rejection, and conformity - Heerdink, Marc W.; Kleef, Gerben A. van; Homan, Astrid C.; Fischer, Agneta H. (Frontiers in Psychology, 2015)
How many members of a group need to express their anger in order to influence a deviant group member's behavior? In two studies, we examine whether an increase in number of angry group members affects the extent to which a deviant individual feels rejected, and we investigate downstream effects on conformity. We show that each additional angry reaction linearly increases the extent to which a deviant individual feels rejected, and that this relation is independent of the total number of majority members (Study 1). This felt rejection is then shown to lead to anti-conformity unless two conditions are met: (1) the deviant is motivated to seek reacceptance in the group, and (2) conformity is instrumental in gaining reacceptance because it is observable by the majority (Study 2). These findings show that angry reactions are likely to trigger anti-conformity in a deviant, but they are also consistent with a motivational account of conformity, in which conformity is strategic behavior aimed at gaining reacceptance from the group.